AB1284 Validity of a computer-assisted manual segmentation software to quantify erosion volume on wrist using computed tomography scans in rheumatoid arthritis. (23rd January 2014) - Carotti, M.; Ariani, A.; Gutierrez, M.; Morbiducci, J.; Gasparini, S.; Grassi, W.; Giuseppetti, G.; Salaffi, F.
Abstract : Objectives: To investigate the performance of radiography for the detection of wrist bone erosions in rheumatoid arthritis (RA) using multidetector computed tomography (CT) as the reference method, and to assess the validity of a computer-assisted manual segmentation software to quantify erosions' volume on wrist CT scans. Methods: With CT as the reference method, the overall sensitivity, specificity and accuracy (concordance) of radiography for detecting erosions were 21.4%, 89.5% and 67.2%, respectively. Erosion volume on CT measurements per subject ranged from 0.001 cm 3 to 2.6 cm 3 . Spearman's RAMRIS score of individual wrist bones in all persons (n=23) correlated with the total erosion volume on CT (p<0.0001) and with the ratio between erosion volume and the corresponding bone volume on a percentage basis (rho=0.944; p<0.0001). The total Sharp/van der Heijde erosion score of the all wrist bones did not correlate with the RAMRIS and total volume erosion measurement on CT (p=0.08, p=0.165, respectively). Results: With CT as the reference method, the overall sensitivity, specificity and accuracy (concordance) of radiography for detecting erosions were 21.4%, 89.5% and 67.2%, respectively. Erosion volume on CT measurements per subject ranged from 0.001 cm 3 to 2.6 cm 3 . Spearman's RAMRIS score of individual wrist bones in all persons (n=23) correlated with the total erosion volume on CT (p<0.0001) and with the ratio between erosion volume and the corresponding bone volume on a percentage basis (rho=0.944; p<0.0001). The total Sharp/van der Heijde erosion score of the all wrist bones did not correlate with the RAMRIS and total volume erosion measurement on CT (p=0.08, p=0.165, respectively). Conclusions: With CT as the reference method, the radiograph showed very low sensitivity. The tested volumetric method was highly correlated to scores of erosions on CT. The volumetric method will require further evaluation in terms of interobserver reliability, with examination of responsiveness in longitudinal studies. References: Rosset et al. OsiriX: an open-source software for navigating in multidimensional DICOM images. J Digit Imaging 2004;17 (3): 205-16. Disclosure of Interest: None Declared